Modified PBAT material, high water vapor barrier biodegradable mulching film and preparation method of high water vapor barrier biodegradable mulching film
By adding epoxidized fatty acid glyceride (EAG) to synthesize modified PBAT materials, the problems of insufficient water vapor barrier performance and degradation of processing performance of PBAT plastic film are solved, and efficient water vapor barrier and mechanical properties are achieved.
Patent Information
- Application Number
- CN202411866228.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing PBAT plastic film has poor water vapor barrier properties, resulting in insufficient moisture retention performance. At the same time, there are problems such as low compatibility between polymers and reduced mechanical properties during the processing process.
During the esterification process, the modified PBAT material is synthesized by adding epoxidized fatty acid glyceride (EAG) to improve the mechanical properties of the material and the water vapor barrier properties through esterification and polycondensation reaction.
It significantly improves the mechanical properties and water vapor barrier properties of modified PBAT materials, solves the problem of insufficient performance of traditional PBAT plastic films, and simplifies the production process, which is suitable for large-scale industrial production.
Smart Images

Figure CN119529252A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of polymer materials, and in particular relates to a modified PBAT material, a high water vapor barrier biodegradable mulch film and a preparation method thereof. Background Art
[0002] Film mulching has become an important agricultural production technology in my country. However, the extensive use of traditional polyethylene film in recent years has led to the accumulation of residual film in farmland, and the growth space of crop roots has been increasingly affected, resulting in reduced absorption and utilization of water and nutrients, and a decline in crop yield and quality, which seriously affects the sustainable development of my country's agriculture.
[0003] Biodegradable mulch is a low-carbon, environmentally friendly material. It not only plays an efficient role in retaining moisture during the germination and seedling stages of crops, preventing the loss of water and heat in the soil, but can also be degraded by microorganisms in the fields to produce water, carbon dioxide, and small molecules after the crops mature, without causing pollution to the soil environment. In agricultural covering applications, using biodegradable mulch instead of traditional mulch is one of the effective means to solve the pollution of residual film in farmland. Polybutylene terephthalate-adipate (PBAT) has excellent mechanical properties and good biodegradability, making it the mainstream material currently used in the field of biodegradable mulch. However, the water vapor barrier performance of PBAT mulch is worse than that of traditional polyethylene mulch, resulting in its insufficient moisture retention performance.
[0004] At present, there are two main technical methods to improve the water vapor barrier performance of PBAT mulch films. One is to add high barrier polymers to make blended films or multilayer films, and the other is to add barrier performance enhancers. Patent CN106221165A discloses a high barrier fully biodegradable mulch film, which uses PPC with excellent barrier properties to melt blend with PBAT and PHBH and blown into film to obtain a high barrier performance PBAT mulch film. Patent CN118596670A discloses a fully biodegradable multilayer mulch film including an aging-resistant layer and a barrier layer. The function is regulated by adjusting the amount of PGA and ultraviolet absorber in the two-layer formula to obtain a PBAT mulch film product with excellent water vapor barrier performance and moderate hardness. Patent CN110452507A discloses a high barrier fully biodegradable mulch film, which improves the barrier performance of the PBAT mulch film by adding a barrier performance enhancer. Barrier performance enhancers mainly include organic barrier performance enhancers such as low molecular weight polyethylene wax, oxidized polyethylene wax, vaseline and 1,4-butanediol, as well as inorganic barrier performance enhancers such as micron-grade talc, nano-grade talc, high-transmittance talc, mica flakes, nano-montmorillonite, modified nano-cellulose and nano-attapulgite. Patent CN118063941A discloses a high-barrier fully biodegradable mulch film, which uses a blend of three degradable materials: PBAT, PHBH and PGA, and uses polymethacrylic acid and ethylene-norbornene copolymer as water vapor barriers to improve the barrier performance of PBAT. However, the technical innovations of the above methods are all concentrated in the processing link. The blending of PBAT with other polymers has the problem of processing and comprehensive performance degradation due to the low compatibility between polymers, which requires complex formula design to solve; the structure of the multi-layer film needs to be realized through multi-formula design and multi-layer co-extrusion process, which has high requirements for processing equipment and processing technology; barrier performance enhancers, especially inorganic barrier performance enhancers, generally have the problem of mechanical properties and aging resistance degradation due to insufficient interface strength, which needs to be solved by modification or adding compatibilizers. Therefore, there is an urgent need for a biodegradable mulch film with good water vapor barrier properties, mechanical properties and aging resistance and a preparation method thereof. Summary of the invention
[0005] The purpose of the present invention is to address the deficiencies in the prior art and to propose a modified PBAT material and a preparation method thereof, wherein the modified PBAT material is synthesized by adding epoxidized fatty acid glyceride (EAG) during the esterification process to improve the mechanical properties and water vapor barrier properties of the material.
[0006] Another object of the present invention is to provide a high water vapor barrier biodegradable mulch film and a preparation method thereof, which is prepared by using the above-mentioned modified PBAT material. The obtained biodegradable mulch film has good water vapor barrier properties, mechanical properties and aging resistance, and the production process is simple. It can be mass-produced industrially using general film blowing equipment.
[0007] The purpose of the present invention is achieved through the following technical solutions.
[0008] The first aspect of the present invention is to provide a modified PBAT material, comprising a reaction product of terephthalic acid, adipic acid, 1,4-butanediol, and epoxidized fatty acid glyceride.
[0009] The epoxidized fatty acid glyceride is selected from at least one of epoxidized rapeseed oil, epoxidized safflower oil, epoxidized linseed oil, epoxidized sunflower oil, epoxidized corn oil, epoxidized olive oil, epoxidized soybean oil, epoxidized peanut oil, epoxidized cottonseed oil and epoxidized palm oil;
[0010] The epoxide value of the epoxidized fatty acid glyceride is 0.1 to 3.0 mol / 100 g, preferably 0.1 to 1.0 mol / 100 g.
[0011] The second aspect of the present invention is to provide a method for preparing the modified PBAT material, comprising the steps of reacting components including terephthalic acid, adipic acid, 1,4-butanediol, and epoxidized fatty acid glyceride to obtain the modified PBAT material;
[0012] Preferably, the preparation method of the modified PBAT material specifically comprises the following steps:
[0013] (1) subjecting adipic acid and epoxidized fatty acid glyceride to a ring-opening reaction to obtain compound ESO-AA;
[0014] (2) subjecting the compound ESO-AA obtained in step (1), 1,4-butanediol and terephthalic acid to an esterification reaction under the action of a catalyst;
[0015] (3) subjecting the esterification reaction product obtained in step (2) to a condensation polymerization reaction to obtain the modified PBAT material.
[0016] Wherein, in the preparation method of the modified PBAT material:
[0017] The molar ratio of terephthalic acid, adipic acid, 1,4-butanediol and epoxidized fatty acid glyceride is 10: (10-100): (20-130): (0.01-5), preferably 10: (10-20): (20-40): (0.05-1);
[0018] The catalyst is selected from at least one of titanium catalysts (such as titanium dioxide, titanate catalysts, etc.), antimony catalysts (such as antimony trioxide, antimony acetate, ethylene glycol antimony, etc.), germanium catalysts (such as germanium dioxide and metal complexes, etc.), and tin catalysts (such as stannous chloride and metal complexes, etc.), preferably at least one of titanate catalysts and antimony catalysts, wherein the titanate catalyst can adopt commonly used titanate compounds, such as but not limited to tetrabutyl titanate, diisopropyl titanate, etc., and the antimony catalyst includes but not limited to antimony trioxide, antimony acetate, ethylene glycol antimony, etc.; the amount of the catalyst used is not particularly limited, and it can be added in a commonly used amount.
[0019] In the preparation method of the modified PBAT material:
[0020] The conditions of the ring-opening reaction are: temperature 160-190° C., time 20-40 min; the ring-opening reaction is preferably carried out under a protective gas atmosphere, and the protective gas can be commonly used nitrogen or inert gas (such as argon);
[0021] The conditions of the esterification reaction are: temperature 140-220° C., time 1-5 h; the esterification reaction is preferably carried out under a protective gas atmosphere, and the protective gas can be commonly used nitrogen or inert gas (such as argon);
[0022] The conditions of the polycondensation reaction are: temperature 240-260° C., pressure <50 Pa, and time 0.2-1.5 h; after the polycondensation reaction, a protective gas (such as nitrogen) is introduced to cool the reaction system.
[0023] The order of adding the components such as ESO-AA, 1,4-butanediol, terephthalic acid, and the catalyst in the esterification reaction process in step (2) is not particularly limited, and can be selected according to the actual reaction. For example, the esterification reaction step in step (2) includes any of the following methods:
[0024] Method (I): Mix the compound ESO-AA, 1,4-butanediol, terephthalic acid and a catalyst and then carry out an esterification reaction; or,
[0025] Method (ii): Esterification reaction of compound ESO-AA and terephthalic acid with 1,4-butanediol in the presence of a catalyst; or,
[0026] Method (three): After the compound ESO-AA, 1,4-butanediol and a catalyst are mixed and reacted, terephthalic acid is added to continue the esterification reaction.
[0027] The third aspect of the present invention is to provide a high water vapor barrier biodegradable mulch film, which is prepared from a modified PBAT material, wherein the modified PBAT material is the modified PBAT material described above. Specifically, the modified PBAT material comprises a reaction product of terephthalic acid, adipic acid, 1,4-butanediol, and epoxidized fatty acid glyceride.
[0028] The thickness of the high water vapor barrier biodegradable mulch film can be adjusted according to the actual needs. For example, the thickness of the high water vapor barrier biodegradable mulch film is 5 to 20 μm; the water vapor permeability of the high water vapor barrier biodegradable mulch film is less than 8×10 -14 g cm / cm 2 ·s·Pa.
[0029] The fourth aspect of the present invention is to provide a method for preparing the above-mentioned high water vapor barrier biodegradable mulch film, comprising blow-molding the components including the modified PBAT material into a film to obtain the high water vapor barrier biodegradable mulch film. The blow-molding film can be achieved using commonly used blow-molding film equipment and process conditions. For example, the blow-molding film conditions are: screw temperature of 140-160°C, screw aspect ratio ≥20:1, and blow ratio ≥2:1.
[0030] The technical solution provided by the present invention has the following technical effects:
[0031] (1) The present invention adds epoxidized fatty acid glyceride (EAG) during the esterification process of PBAT synthesis to obtain a modified PBAT material, the mechanical properties and aging resistance of which are significantly improved, and the water vapor barrier rate can be increased by more than 5 times, breaking through the current technical bottleneck in the performance of biodegradable mulch films.
[0032] (2) The present invention directly blows the modified PBAT material (EAG-PBAT) into a film to obtain a high water vapor barrier biodegradable mulch film. Different from the existing technology using melt blending modification or composite modification, the present invention avoids the performance degradation and poor compatibility problems caused by melt processing to prepare the modified components.
[0033] (3) The raw materials for preparing the high water vapor barrier biodegradable mulch film of the present invention are easily available and the production process is simple. By technically modifying the existing PBAT polymerization process and using general film blowing equipment, large-scale industrial production can be achieved. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a Fourier transform infrared spectra of the modified PBAT materials obtained in Examples 1 to 3 of the present invention, the PBAT material obtained in Comparative Example 1, and ESO (epoxidized soybean oil).
[0035] Figure 2The nuclear magnetic resonance hydrogen spectra of the modified PBAT materials obtained in Examples 1 to 3 of the present invention and the PBAT material obtained in Comparative Example 1 are shown.
[0036] Figure 3 The tensile strength and tensile strength retention rate of the ESO-PBAT mulch obtained in Examples 4 to 6 of the present invention and the PBAT mulch obtained in Comparative Example 2 before and after 100 hours of aging in the transverse and longitudinal directions. TD represents the transverse direction, MD represents the longitudinal direction, the abscissa represents the test sample, the left ordinate represents the tensile strength (MPa), and the right ordinate represents the tensile strength retention rate (%).
[0037] Figure 4 The elongation at break and retention rates in the transverse and longitudinal directions of the ESO-PBAT mulch films obtained in Examples 4 to 6 of the present invention and the PBAT mulch films obtained in Comparative Example 2 before and after 100 hours of aging. TD represents the transverse direction, MD represents the longitudinal direction, the abscissa represents the test sample, the left ordinate represents the elongation at break (%), and the right ordinate represents the retention rate of the elongation at break (%).
[0038] Figure 5 The water vapor barrier properties of the ESO-PBAT mulch obtained in Examples 4 to 6 of the present invention and the PBAT mulch obtained in Comparative Example 2. The horizontal axis is the test sample, and the vertical axis is the water vapor permeability coefficient (10 -14 g cm / cm 2 ·s·Pa). DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with specific embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.
[0040] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0041] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0042] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0043] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to those skilled in the art. The present application description and examples are exemplary only.
[0044] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0045] The sources of raw materials used in the following examples of the present invention are as follows:
[0046] Terephthalic acid (TA), adipic acid (AA), 1,4-butanediol (1,4-BDO), tetrabutyl titanate (TBOT), and antimony trioxide were purchased from Aladdin Biochemical Technology Co., Ltd.;
[0047] Epoxidized soybean oil (ESO) was purchased from Shanghai MacLean Biochemical Technology Co., Ltd., with an epoxide value of 0.4 mol / 100 g.
[0048] The product characterization method used in the present invention is as follows:
[0049] Fourier transform infrared spectroscopy (FTIR): performed on a Nicolet LSJ20 instrument with a resolution of 4 cm -1 , scanning frequency is 32 times, range is 400~4000cm -1 .
[0050] H NMR ( 1 H NMR) was carried out on a Bruker Avance III HD 500 MHz instrument with CDCl3 as solvent.
[0051] Tensile performance test: carried out on a SANS CMT6104 instrument in accordance with GB / T1040.3-2018, with a tensile speed of 100 mm / min.
[0052] Water vapor barrier performance test: carried out on Labthink C360M instrument according to GB / T1037-2021, temperature is 23℃, relative humidity is 50%.
[0053] Biodegradability test: According to GB / T 22047-2008, the method of measuring oxygen demand in a closed respirometer is adopted.
[0054] Example 1 Preparation of modified PBAT material
[0055] The preparation of modified PBAT material includes the following steps:
[0056] (1) Ring-opening reaction: Epoxidized soybean oil (ESO) and adipic acid (AA) were mixed in a molar ratio of 1:80 and reacted at 180° C. for 30 min under a nitrogen atmosphere to obtain ESO-AA.
[0057] (2) Esterification reaction: 1,4-butanediol (1,4-BDO) with a molar ratio of 2.4 times that of adipic acid (AA) and tetrabutyl titanate (TBOT) with a molar ratio of 1,4-butanediol to TBOT of 90:1 were added to the ESO-AA product after the reaction in step (1), and the mixture was reacted at 160° C. for 1 h under a nitrogen atmosphere; then terephthalic acid (TA) and antimony trioxide were added to the system at a molar ratio of adipic acid, terephthalic acid and antimony trioxide of 100:100:3, and the temperature was raised to 200° C. for reaction for 3 h.
[0058] (3) Condensation reaction: The system pressure was controlled at <50 Pa, and the temperature was slowly raised to 260°C within 1 hour. After the reaction lasted for 1 hour, N2 was introduced to cool the system to room temperature to obtain the modified PBAT resin ESO-PBAT.
[0059] Example 2 Preparation of modified PBAT material
[0060] The preparation process of the modified PBAT material is the same as that of Example 1, except that the molar ratio of epoxidized soybean oil to adipic acid is 1:100.
[0061] Example 3 Preparation of modified PBAT material
[0062] The preparation process of the modified PBAT material is the same as that of Example 1, except that the molar ratio of epoxidized soybean oil to adipic acid is 1:120.
[0063] Comparative Example 1 Preparation of PBAT Material
[0064] The preparation process of the modified PBAT material is the same as that of Example 1, except that the epoxy soybean oil is not added. The preparation of the PBAT material includes the following steps:
[0065] (1) Esterification reaction: Adipic acid (AA) and 1,4-butanediol (1,4-BDO) in a molar ratio of 1:2.4 and 1,4-butanediol and tetrabutyl titanate (TBOT) in a molar ratio of 90:1 were mixed and reacted at 160°C for 1 h under a nitrogen atmosphere; then terephthalic acid (TA) and antimony trioxide were added to the system in a molar ratio of adipic acid, terephthalic acid, and antimony trioxide of 100:100:3, and the temperature was raised to 200°C for reaction for 3 h.
[0066] (2) Condensation reaction: The system pressure was controlled at <50 Pa, and the temperature was slowly raised to 260°C within 1 hour. After the reaction lasted for 1 hour, N2 was introduced to cool the system to room temperature to obtain PBAT resin.
[0067] Test Example 1 Test of modified PBAT material
[0068] like Figure 1 As shown, the ESO-PBAT prepared in Examples 1 to 3 showed a peak at 827 cm -1 The characteristic peak of epoxy in ESO-PBAT increases with the increase of ESO content. -1 The -C=O stretching vibration peak at 1410 cm -1 The relative intensity of the -CH2- bending vibration peak at Figure 2 As shown in the figure, a new peak at 3.69-3.75 ppm appeared in ESO-PBAT, which is the methyl proton signal peak connected to the hydroxyl group in β-hydroxy ester; in addition, methylene and methyl proton peaks in the ESO structure appeared at 0.85-0.90 ppm and 1.25-1.35 ppm, respectively. From the proton peaks in β-hydroxy ester and ESO fragments that are enhanced with the increase of ESO dosage, it can be inferred that the abundance of ESO fragments in ESO-PBAT depends on the amount of its monomer.
[0069] Example 4 Preparation of high water vapor barrier biodegradable mulch film
[0070] The modified PBAT material ESO-PBAT prepared in Example 1 was crushed and then extruded and blown to prepare an ESO-PBAT ground film, the screw processing temperature of the film blowing device was 160°C, the head temperature was 140°C, the screw aspect ratio was 20:1, and the blowing ratio was 2:1. A uniform ESO-PBAT ground film with a thickness of about 10 μm was obtained.
[0071] Example 5 Preparation of high water vapor barrier biodegradable mulch film
[0072] The preparation method of the high water vapor barrier biodegradable mulch film is the same as that of Example 4, except that the modified PBAT material used is the ESO-PBAT prepared in Example 2.
[0073] Example 6 Preparation of high water vapor barrier biodegradable mulch film
[0074] The preparation method of the high water vapor barrier biodegradable mulch film is the same as that of Example 4, except that the modified PBAT material used is the ESO-PBAT prepared in Example 3.
[0075] Comparative Example 2 Preparation of biodegradable mulch film
[0076] The preparation method of the biodegradable mulch film is the same as that of Example 4, except that the PBAT resin used is the PBAT resin prepared in Comparative Example 1.
[0077] Test Example 2 Test of high water vapor barrier biodegradable mulch film
[0078] The PBAT mulch films prepared in Examples 4 to 6 and Comparative Example 1 were subjected to laboratory artificial weathering experiments. According to GB / T 16422.2-2014, an Atlas test chamber (Ci 4000) equipped with a 6500W xenon lamp was used to test the artificial weathering performance of the mulch film. The blackboard temperature (BPT) of the darkroom was 65°C and the relative humidity (RH) was 50%. A 2h exposure cycle was used, and each cycle included 108min of UV radiation and 12min of simultaneous water spraying and UV radiation. The incident light irradiation intensity was 0.55W / m 2 , wavelength is 340nm. After 100h of artificial weathering, the samples were taken out for tensile property test.
[0079] like Figure 3 As shown, compared with the PBAT mulch film without ESO monomer introduced in Comparative Example 2, the ESO-PBAT mulch films prepared in Examples 4 to 6 have a transverse tensile strength increased by more than 10% and a longitudinal tensile strength increased by more than 28%, and the improvement effect gradually increases with the increase in the amount of ESO introduced. Figure 4 As shown, compared with the PBAT mulch without the introduction of ESO monomer in Comparative Example 2, the transverse elongation at break of the ESO-PBAT mulch prepared in Examples 4 to 6 increased by more than 100%, and the longitudinal elongation at break increased by more than 15%, and the improvement effect gradually increased with the increase of the amount of ESO introduced. After 100 hours of artificial weather aging, the transverse tensile strength retention rate increased from 71% to 95%, and the longitudinal tensile strength retention rate increased from 76% to 95%; the transverse elongation at break retention rate increased from 70% to 86%, and the longitudinal elongation at break retention rate increased from 66% to 80%, and the retention rate improvement effect gradually increased with the increase of the amount of ESO introduced, indicating that the introduction of ESO has a significant effect on the tensile properties and aging resistance of the ESO-PBAT mulch, and the improvement effect is positively correlated with the amount of ESO introduced.
[0080] like Figure 5As shown in the figure, the water vapor permeability of the PBAT mulch film in Comparative Example 2 without the introduction of ESO monomer is 3.23×10 -13 g cm / cm 2 ·s·Pa, the introduction of ESO in Examples 4 to 6 can reduce the water vapor transmission rate of the ESO-PBAT mulch to 5.28×10 -14 g cm / cm 2 ·s·Pa, the water vapor barrier performance was improved by more than 5 times, and the water vapor permeability of the ESO-PBAT mulch gradually decreased with the increase of the amount of ESO introduced, indicating that the introduction of ESO has a significant effect on improving the water vapor barrier performance of the ESO-PBAT mulch, and the improvement effect is positively correlated with the amount of ESO introduced.
[0081] The relative biodegradability of the mulch prepared in Examples 4 to 6 reached more than 90%, and the required time was 117 days, 113 days and 98 days, respectively, all lower than 180 days, indicating that the biodegradability of the ESO-PBAT mulch meets the requirements of GB / T 35795-2017.
[0082] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present invention is within the protection scope of the present invention.
Claims
1. A modified PBAT material comprising a reaction product of terephthalic acid, adipic acid, 1,4-butanediol, and epoxidized fatty acid glyceride.
2. The modified PBAT material according to claim 1, characterized in that: The epoxidized fatty acid glyceride is selected from at least one of epoxidized rapeseed oil, epoxidized safflower oil, epoxidized linseed oil, epoxidized sunflower oil, epoxidized corn oil, epoxidized olive oil, epoxidized soybean oil, epoxidized peanut oil, epoxidized cottonseed oil and epoxidized palm oil; and / or, The epoxide value of the epoxidized fatty acid glyceride is 0.1 to 3.0 mol / 100 g, preferably 0.1 to 1.0 mol / 100 g.
3. A method for preparing the modified PBAT material according to any one of claims 1 to 2, comprising the step of reacting components including terephthalic acid, adipic acid, 1,4-butanediol, and epoxidized fatty acid glyceride to obtain the modified PBAT material; Preferably, the preparation method of the modified PBAT material specifically comprises the following steps: (1) subjecting adipic acid and epoxidized fatty acid glyceride to a ring-opening reaction to obtain compound ESO-AA; (2) subjecting the compound ESO-AA obtained in step (1), 1,4-butanediol and terephthalic acid to an esterification reaction under the action of a catalyst; (3) subjecting the esterification reaction product obtained in step (2) to a condensation polymerization reaction to obtain the modified PBAT material.
4. The preparation method according to claim 3, characterized in that: The molar ratio of terephthalic acid, adipic acid, 1,4-butanediol and epoxidized fatty acid glyceride is 10:(10-100):(20-130):(0.01-5), preferably 10:(10-20):(20-40):(0.05-1); and / or, The catalyst is selected from at least one of titanium-based catalysts, antimony-based catalysts, germanium-based catalysts, and tin-based catalysts, and is preferably selected from at least one of titanate-based catalysts and antimony-based catalysts.
5. The preparation method according to claim 3, characterized in that: The conditions of the ring-opening reaction are: temperature 160-190° C., time 20-40 min; and / or, The conditions of the esterification reaction are: temperature 140-220° C., time 1-5 h; and / or, The conditions of the polycondensation reaction are: temperature 240-260° C., pressure <50 Pa, and time 0.2-1.5 h.
6. The preparation method according to claim 3, characterized in that: The esterification step in step (2) includes any of the following methods: Method (I): Mix the compound ESO-AA, 1,4-butanediol, terephthalic acid and a catalyst and then carry out an esterification reaction; or, Method (ii): Esterification reaction of compound ESO-AA and terephthalic acid with 1,4-butanediol in the presence of a catalyst; or, Method (three): After the compound ESO-AA, 1,4-butanediol and a catalyst are mixed and reacted, terephthalic acid is added to continue the esterification reaction.
7. A high water vapor barrier biodegradable mulch film prepared from a modified PBAT material, wherein the modified PBAT material is the modified PBAT material according to any one of claims 1 to 2 or the modified PBAT material obtained by the preparation method according to any one of claims 3 to 6.
8. The high water vapor barrier biodegradable mulch film according to claim 7, characterized in that: The thickness of the high water vapor barrier biodegradable mulch film is 5 to 20 μm; and / or, The water vapor permeability of the high water vapor barrier biodegradable mulch film is less than 8×10 -14 g cm / cm 2 ·s·Pa.
9. A method for preparing the high water vapor barrier biodegradable mulch film according to claim 7 or 8, comprising blowing the components including the modified PBAT material into a film to obtain the high water vapor barrier biodegradable mulch film.
10. The preparation method according to claim 9, characterized in that: The conditions for the blow molding film are: a screw temperature of 140-160° C., a screw aspect ratio of ≥20:1, and a blow-up ratio of ≥2:1.
Citation Information
Patent Citations
High-barrier full-biodegrade mulching film and preparation method thereof
CN106221165A
High-barrier high-strength ultrathin full-biodegradable mulching film and preparation method
CN110452507A
High-barrier full-biodegradable mulching film and preparation method thereof
CN118063941A
Full-biodegradable multilayer mulching film and preparation method thereof
CN118596670A
Biaxially oriented epoxidised fatty acid derivatives containing hydrolysis resistant polyester film and method for production of same and use of same
CN101899198A